Corrosion behavior of Al-6.8Zn-2.2Mg-Sc-Zr alloy with high resistance to intergranular corrosion - Yuexing Liang; Guoai Li; Li Liu; Jiantang Jiang; Jian Cao; Wenzhu Shao; Liang Zhen (Journal of Materials Research and Technology, 2023)
A high-strength and anti-intergranular corrosion (IGC) Al-6.8Zn-2.2 Mg-Sc-Zr alloy (AS alloy) was designed, and the effects of Sc addition and Cu removal on the microstructure, mechanical properties and corrosion behavior were systematically investigated. Based on transmission electron microscopy (TEM) and Kelvin probe force microscopy (KPFM) techniques, the underlying causes of IGC and exfoliation corrosion (EXCO) of the AS alloy were investigated, and the corrosion mechanism of AS alloy was finally obtained. The AS alloy exhibits excellent mechanical properties with a tensile strength of 601 MPa in the peak-ageing condition at 120 °C, which comes from the pinning effect of Al3(Sc, Zr) dispersions. Moreover, AS alloys of T6 and T74 conditions show outstanding IGC and EXCO resistance. On the one hand, the fine, near-ellipsoidal grains in AS alloy alleviate the peeling stress caused by IGC products by blocking the formation of wedge-shaped gaps along GBs, which then bring about improved EXCO resistance. On the other hand, the removal of Cu from the traditional Al-Zn-Mg-Cu alloy avoids the segregation of Cu into GBs and thereafter reduces the fluctuations of the potential and the electron work function (EWF) across the GBs; the addition of Sc induces the high fraction of LAGBs and thus weakens the solutes' segregation at GBs, which can be beneficial for smoothing the fluctuation of corrosion potential (Ecorr) to enhance the IGC resistance.